Measuring Consumer-Based Brand Equity: The Use Of Foreign Languages As Hotel Names - Faerrosa, Lady; Pratama, Aryan Agus (Value : Jurnal Manajemen dan Akuntansi, 2024)
Hotel naming strategies are an important issue to study when a tourist destination targets both domestic and foreign tourists at the same time. This research aims to describe four dimensions of consumer-based brand equity (brand awareness, brand association, perceived quality, and brand loyalty) related to naming hotels in foreign languages on Lombok Island. The method used is a quantitative descriptive analysis with an unknown population, so a sample of 272 respondents was determined with an error rate of 10%. The data obtained was analyzed using basic statistics with the help of SPSS. The research results show that the majority of respondents who are domestic tourists in this study are aware of the foreign language used in naming hotels on Lombok Island., they think that the use of foreign languages is cooler and unique and that the hotels have more up-to-date facilities, and they often book hotels with foreign name. The results of this research can be a reference for marketers and hotel owners to determine hotel naming strategies that are more appropriate to their target consumers so that they can be better accepted by the market.